A feasibility assessment of a retrofit Molten Carbonate Fuel Cell coal-fired plant for flue gas CO2 segregation. (21st April 2021) - Cooper, R.; Bove, D.; Audasso, E.; Ferrari, M.C.; Bosio, B.
Abstract: This work considers the use of a Molten Carbonate Fuel Cell (MCFC) system as a power generation and CO2 concentrator unit downstream of the coal burner of an existing production plant. In this way, the capability of MCFCs for CO2 segregation, which today is studied primarily in reference to large-scale plants, is applied to an intermediate-size plant highlighting the potential for MCFC use as a low energy method of carbon capture. A technical feasibility analysis was performed using an MCFC system-integrated model capable of determining steady-state performance across varying feed composition. The MCFC user model was implemented in Aspen Custom Modeler and integrated into the reference plant in Aspen Plus. The model considers electrochemical, thermal, and mass balance effects to simulate cell electrical and CO2 segregation performance. Results obtained suggest a specific energy requirement of 1.41 MJ kg CO2 −1 significantly lower than seen in conventional Monoethanolamine (MEA) capture processes. Highlights: An MCFC system has been tested for carbon capture downstream a coal burner. A local balance model was used to specifically analyse the MCFC performance. MCFC can improve the system efficiency compared to other solutions.